GAYA BAHASA BERDASARKAN STRUKTUR KALIMAT DALAM PANTUN ADAT JAMBI - pri yanto (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2016)
The purpose of this research is to describe the style of language based on the structure of the sentence contained in the traditional pantun Jambi. The method used in this research is a qualitative descriptive method, with a stylistic approach. The data in this study is the style of language based on sentence structure. The data source in the research is the rhyme contained in the book "Principles of Traditional Shoot Jambi Nine Village Head Jilid III Customary Literature Jambi". The results of this study indicate that the style of language based on the sentence structure found in the Jambi customs pantun is (a) the climactic language style, (b) the style of the language of parallelism, (c) the anaforal reprocessing language style, (d) the repetition style of mesodiplosis, (e) repetition of anadiplosis, (f) epistrofa reps.